2003
DOI: 10.1186/cc1888
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionUse of the Bair Hugger forced-air patient warming system during prolonged abdominal vascular surgery may lead to increased bacterial contamination of the surgical field by mobilization of the patient's skin flora.MethodsThis possibility was studied by analyzing bacterial content in air and wound specimens collected during surgery in 16 patients undergoing abdominal vascular prosthetic graft insertion procedure, using the Bair Hugger patient warming system. The bacterial colony counts from the begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The effect of FAW on contaminant counts in the sterile OR environment ( 12 , 25 , 26 , 31 ) generated different opinions among different authors. Studies conducted by Albrecht et al found an increased bacterial load in OR room with ultra clean ventilation (UCV) when FAW is used, and attributed this effect to the floor level location of FAW blowers and their intake, where most of the contaminants originated ( 4 , 6 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of FAW on contaminant counts in the sterile OR environment ( 12 , 25 , 26 , 31 ) generated different opinions among different authors. Studies conducted by Albrecht et al found an increased bacterial load in OR room with ultra clean ventilation (UCV) when FAW is used, and attributed this effect to the floor level location of FAW blowers and their intake, where most of the contaminants originated ( 4 , 6 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies used particle count in air samples to assess the air quality in OR and concluded that FAW does not worsen air quality in laminar flow operating room ( 2 , 14 , 25 , 26 , 31 ). Cristina et al found no statistically significant correlation between microbial loads and particle counts when assessing OR air quality ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Placement of these devices is often limited due to interference with the surgical field, and they pose a potential risk of thermal burns due to direct contact with patient skin. [16][17][18][19] Some studies [20][21][22][23][24][25] suggest that forced warm air blowers increase the risk of bacterial contamination of the surgical site; however, this remains controversial. In the present study, no surgical site infections were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Convection patient warmers are commonly used on patients in operating rooms to prevent or mitigate hypothermia; however, there are concerns that these devices may not only harbor bacteria and dust but mobilize infectious particles that could potentially seed wounds. 17 , 18 Their internal fans can disturb air flow currents in an operating room, causing dust, debris, and/or bacteria to settle on the sterile field. 19 …”
Section: Identifying Addressable Factorsmentioning
confidence: 99%